Mathematical evaluation of the influence of multiple factors on implant stability quotient values in clinical practice: a retrospective study - Huang H; Wismeijer D; Shao X; Wu G (Dove Medical Press, 2016)
Hairong Huang,1 Daniel Wismeijer,1 Xianhong Shao,2 Gang Wu1 1Department of Oral Implantology and Prosthetic Dentistry, Academic Centre for Dentistry Amsterdam (ACTA), MOVE Research Institute, VU University Amsterdam and University of Amsterdam, Amsterdam, Nord-Holland, the Netherlands; 2Best & Easy Dental Clinic, Hangzhou, Zhejiang Province, People’s Republic of China Objectives: The objective of this study is to mathematically evaluate the influence of multiple factors on implant stability quotient values in clinical practice.Patients and methods: Resonance frequency analysis was performed at T1 (measured immediately at the time of implant placement) and at T2 (measured before dental restoration) in 177 patients (329 implants). Using a multivariate linear regression model, we analyzed the influence of the following eleven candidate factors: sex, age, maxillary/mandibular location, bone type, immediate/delayed implantation, bone grafting (presence or absence), insertion torque, I-/II-stage healing pattern, implant diameter, implant length, and T1–T2 time interval.Results: The following factors were identified to significantly influence the implant stability quotient (ISQ) values at T1: insertion torque, bone grafting, I-/II-stage healing pattern, immediate/delayed implantation, maxillary/mandibular location, implant diameter, and sex. In contrast, the ISQ values at T2 were significantly influenced only by three factors: implant diameter, T1–T2 time interval, and insertion torque.Conclusion: Among the eleven candidate factors, seven key factors were found to influence the T1-ISQ values, while only three key factors influenced the T2-ISQ values. Both T1 and T2-ISQ values were found to be influenced by implant diameter and insertion torque. T1 was influenced specifically by the sex of the patient, the location (maxillary or mandibular), the implantation mode (immediate/delayed implantation), the healing stage, and the absence or presence of bone graft materials. Keywords: resonance frequency analysis, implant stability quotient, dental implant, immediate implantation, delayed implantation, insertion torque